Exploring relationships between psychological factors and coping mechanisms in doctors of Delhi NCR: a correlational study - Alam, Viqar; Srivastava, Rani; Kumar, Ashok (International Journal of Research in Medical Sciences, 2025)
Background: The COVID-19 pandemic has posed substantial mental health challenges for healthcare professionals. While pandemic-related anxiety and fear of COVID-19 have been studied, less is known about how these factors relate to general psychological distress and coping styles among physicians in real-world settings. Methods: This study is an observational, cross-sectional analysis involving N=100 physicians. Participants completed the General Health Questionnaire (GHQ) to assess general psychological distress and overall health status, the Coronavirus Anxiety Scale (CAS) to measure coronavirus-specific anxiety, the Fear of COVID-19 Scale (FCV-19S) to evaluate fear related to COVID-19 and the Coping Inventory to assess coping styles. Pearson correlations were computed to examine the inter-correlations among these variables. Results: Coronavirus anxiety was strongly negatively correlated with perceived general health (r=-0.613, p<0.001), indicating that higher anxiety is linked to poorer health perception. Fear of COVID-19 showed a weak but significant positive correlation with general health (r=0.169, p=0.047), suggesting a nuanced relationship between health status and fear. No significant correlations were found between anxiety and coping strategies, nor between coping strategies and overall health, highlighting the complexity of coping mechanisms in this context. Conclusions: The strong negative link between coronavirus-specific anxiety and perceived general health underscores the need for targeted mental health resources within healthcare settings to safeguard physicians’ overall well-being and job performance. Our findings support implementing balanced psychoeducational and resilience-building programs that promote vigilant but non-dysregulated emotional responses, thereby sustaining both physician health and quality of patient care in ongoing and future health crises.